W świecie poznanych i „niepoznanych” liter, czyli o kontynuacji bezsensów w instytucjonalnych praktykach nauki czytania i pisania dzieci - Marzenna Nowicka (Problemy Wczesnej Edukacji)
Reading is a key competence in a social functioning. In the Polish educational system both kindergarten and school, are responsible for the effects of learning this skill. The article presents the results of research on the content of textbooks and methodological guides intended for the basic reading course for children aged six and seven. As a result of the comparison, it was found that the literacy process was doubled at the school level according to the scheme in force in the kindergarten. The page layout for entering a new letter and the suggested exercises are repeated in the textbooks. The same process for introducing a new letter is valid at the kindergarten and on the school level. The texts for learning to read are trivial, and the instructions formulated to them block the development of reading skills at the semantic and critical-creative level.